Larvicidal activities of Bacillus thuringiensis H-14 and Bacillus sphaericus 1593 against three species of mosquitoes of disease vectors in Java - Sugeng Juwono Mardihusodo, Sugeng Juwono Mardihusodo (Universitas Gadjah Mada, 1992)
Bacillus thuringiensis H-14 and Bac. sphaericus 1593 are quite promising as biological control agents utilized as alternatives of chemical insecticides in controlling mosquitoes of disease vectors.The present studies are aimed at determining the larvicidal activitiesÃ¢â¬Â¢of Bac. thuringiensis H-14 and Bac. sphaericus 1593 against Aedes aegypti, Culex quinquefasciatus and Anopheles aconitus, respectively recorded as the main vectors of dengue haemorrhagic fever, bancroftian filariasis and Malaria in Java.Two types of primary powder of Bac. thuringiensis H-14 (IPS 82) and Bac. sphaericus 1593 (RB 80) were tested on their respective activities against larval stages of the three species of mosquitoes under laboratory conditions.It was concluded that, ranked from the high to low level, Bac. thuringiensis H-14 was larvicidal to Ae. aegypti, Cx. quinquefasciatus and An. aconitus, whereas B. sphaericus 1593 was larvicidal to Cx. quinquefasciatus, An. aconitus and Ae. aegypti mosquitoes.Key Words: Bacillus thuringiensis H-14 - Bacillus spaericus 1593 - Aedes aegypti - Culex quinquefasciatus - Anopheles aconitus